Multidisciplinary management of intracardiac tumor thrombus in low-grade endometrial stromal sarcoma: case report and literature review - Zhang, Hanke; Chen, Jinhua; Yang, Chao; Chen, Si; Wang, Miao; Xin, Xiaoyan; Wang, Hongbo; Zhu, Xiaowu (Frontiers in Oncology, 2025)
The low-grade endometrial stromal sarcoma (LG-ESS) represents a slowly proliferating subtype of endometrial stromal tumor but exhibits a preference for late-stage recurrence. Incidence of invasion into major blood vessels and the heart is exceedingly uncommon in this particular neoplasm. We describe a patient with recurrent LG-ESS whose tumor mainly involved the right ovary and right kidney and extended from the ovarian vein to the right atrium. Furthermore, we comprehensively review existing literature on 35 patients exhibiting similar manifestations. In these 36 cases, tumor thrombus primarily extended to the inferior vena cava (n=17), with a minority extending to the right atrium (n=12), while no cases were detected when the tumor thrombus had just extended to the iliac blood vessels, indicating that LG-ESS exhibits an insidious onset during early-stage vascular invasion. It is advisable for comprehensive examination and diligent follow-up in high-risk patients. 19 cases with complete tumor resection were followed up, and all except two patients remained alive with no evidence of disease. Among the 5 cases of mortality, 2 cases did not undergo surgical intervention, while in 3 cases where surgery was performed, complete tumor resection could not be achieved. The causes of death in these patients were related to disease progression or concurrent cardiovascular events. These findings underscore the importance of cytoreductive surgery adhering to the tumor-free principle, or at least removing the lesions in the major blood vessels and heart to prevent acute embolism and sudden demise, which usually requires multidisciplinary teamwork.